Efficiency of antioxidants in some chemical traits of the fruits and leaves for two varieties of tissue culture date palm Phoenix dactylifera L. - Odeh , Maryam M.; Obaid, Nada A.; Abd, Abdulkareem M. (Basrah Journal Of Date Palm Research, 2023)
This study was conducted during the growth season (2022-2023) in a private orchard in the Hartha district - Al-Masheeb area in the north of Basrah province to study the effect of the variety factor. Two varieties of date palm, Barhi and Zamli, were selected, and the second factor was the use of antioxidants tocopherol and Glutathione at three concentrations (0, 75, 150 mg. L-1) for each and the interaction between them in the chemical characteristics of the fruits and leaves of the date fruits, and the number of sprayings starting from the date (10/10/2022) and there were 30 days between one spraying and the next. The results of the study showed that there are significant differences between the varieties in the chemical characteristics of the fruits and leaves (Water content, dry matter, total chlorophyll, and carbohydrates), while there was no significant difference between the varieties in the proline content of leaves. The results also indicated that spraying with antioxidants had a significant effect on the chemical characteristics of dates and leaves, as the treatment (tocopherol 150 + glutathione 150 mg. L-1) was superior. Recording the lowest percentage of water content and the amino acid proline compared to the comparison treatment, which recorded the highest percentage of them (40.29%, 16.26 micrograms. Gm-1). While the same treatment (Tocopherol 150 + Glutathione 150 mg. L-1) excelled in giving the highest percentage of dry matter for dates, amounting to (59.70%). As for the total chlorophyll content of the leaves, it was significantly superior to the treatment (Tocopherol 75 mg. L-1), as it recorded the highest content of chlorophyll, which reached (3.878 mg. 100 gm-1) compared to the comparison treatment, which recorded the lowest content of total chlorophyll, amounting to (1,859 mg 100 gm-1). The treatment (Glutathione 150 mg.L-1) also excelled by recording the highest content of total second carbohydrates, amounting to (28.75%). The second intervention also had a significant effect In the chemical properties of leaves and fruits.